INTEGRASI SAINS DAN ILMU KEISLAMAN - Rochim, Abdul; Nursyam, Nursyam; Cholil, Mufida (Kreatif: Jurnal Pemikiran Pendidikan Agama Islam, 2026)
This study examines the thought of Abu Yusuf Ya‘qub ibn Ishaq al-Kindī (801–873 CE) as a pioneer in integrating the rational sciences (science and philosophy) with Islamic disciplines in the classical Islamic intellectual tradition. Using a historical-analytical approach through a literature review, the article analyzes al-Kindī’s works and secondary studies to map his conceptions of the sources of knowledge, the status of reason, and the relationship between philosophical demonstration and the authority of revelation. The analysis situates al-Kindī’s ideas within the context of the translation movement and the reception of Greek philosophy, and then compares them with the needs of contemporary Islamic scholarship. The findings show that al-Kindī affirms that the truth of philosophy does not contradict the truth of revelation, since both ultimately derive from the same source—God. His views on intellect (al-‘aql), cosmology, and ethics demonstrate a systematic effort to bridge the Hellenistic tradition with Islamic values without undermining the authority of religious texts. The relevance of his thought today is evident in strengthening the paradigm of integrating religious knowledge and modern science, particularly as a conceptual foundation for curricula, research, and academic culture in Islamic educational institutions in Indonesia. This article highlights al-Kindī’s contribution to shaping a scientific attitude that is critical, dialogical, and responsible, while also offering a theoretical reference for responding to multidisciplinary challenges, the secularization of knowledge, and the fragmentation of disciplines in the public sphere. The implication is that the integration of knowledge needs to be developed through philosophical literacy, methodological strengthening, and a tawḥīd-based ethics of scholarship within Islamic education.